The role of sports integration in developing some personality traits among the physically handicapped - Hamdini, Ishak; Mehidi , Mohamed; Barkat , Abd Elhak (sports creativity, 2025)
We examined in our research the effect of sports integration in development of some personality traits the physically handicapped, and similar to the previous studies wich are few, especially Arabic one, this study aimed to identify the effect of sports integration in development of some personality traits to the physically disabled.The study community consisted of Al-Hodnah Basketball Club for wheelchairs, who number 44 athletes, the study was applied to an intentional sample of 44 athletes, and the researcher used the comparative descriptive method, with the use of the main study instrument is the Freiburg scal